Remote monitoring and alert system of HV transformer based on FMEA - Farzin Asadi; Satree Phumpho; Sawai Pongswatd (My University, 2020)
This paper presents a technique to measure and collect maintenance data for remote monitor of high voltage transformer. The technique installs field instruments to measure winding temperature, cooling-oil temperature, inner pressure, electrical power, and so on. IoT2040 is applied for acquisition (DAQ), processing unit and smart gateway. It converts field data into information that enables for real time monitoring and preventive maintenance applications. This technique can transform time-based maintenance to condition-based maintenance. In addition, the proposed script functions are created based on failure modes and effects analysis (FMEA) to identify alarm and alert conditions. Consideration alarm-referenced parameters that are diagnostic, performance/efficiency analysis relate to operation or communication conditions also assign by script functions. The relevant data from IoT2040 can be transmitted to the local computer as well as a remote-mobile devices running the dashboard with Ubidots server. Ubidots server is responsible for HMI and delivering specific alarm and alert services to the user. Users can access for remote monitoring by smart phone, tablet, laptop, and PC. The experiment performs by simulation with 3 phase Oil immersed distribution transformer. Electrical specification is 50 Hz 250 kVA, 22 kV, 400/230 V. The results shown the assigned data, dashboard, and notices message that notices relate the FMEA scripts. The technique provides early warning detection of transformer statuses that make opportunity to take corrective action to prevent failure.
Keywords: Trouble shooting; Dashboard; Laptop; Condition Monitoring; Power Transformer Diagnostics and Insulation